Somewhat Opinionated An American dance journal - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2006)
A letter from America: New York State Theatre 3 January-26 February. Joyce Theatre, New York City 17 January. Joyce Theatre 7 February. New York State Theatre 12 February. Joyce Theatre 15 February. Bass Hall, Forth Worth, Texas 17 February. New York City Center 23-26 February. New York City Center 28 February-19 March. Brooklyn Academy of Music 15-26 March. N. J. Performing Arts Center, Newak, New Jersey 17 March. PALABRAS CLAVE: New York City Ballet, Netherlands, Emio Greco, Pieter C. Scholten, Ronald K. Brown, Evidence, Solomon Tencer, Ben Stevenson, Kings of the Dance, Paul Taylor Dance Company, Mark Morris Dance Group, The Tchaikovsky Perm Ballet.